ANALISIS FAKTOR YANG MENJADI PENENTU MAHASISWA DALAM MEMILIH PERGURUAN TINGGI - Endang Ruhiyat (Inovasi, 2016)
ANALYSIS OF FACTORS DETERMINANT STUDENTS IN CHOOSING UNIVERSITY. Background on why this research is due to intense competition in the "industry" of higher education in Indonesia with the emergence of a new university in a market segment that is still wide. This affects the interest of students to go to college at the University Pamulang phenomenal. This study aims to determine the determinants that influence decisions in choosing a college student at the University Pamulang. Data were collected by distributing questionnaires to 100 active students Pamulang University which is a sample of all the faculties obtained by using proportional sampling technique so that samples can be dispersed. This study uses factor analysis performed on 23 variables that influence decisions in choosing a college student at the University Pamulang. The results of factor analysis showed that a reduction in the variable of 23 variables to 21 variables. Variables that were excluded from the analysis of the factors are variable economic conditions, it is because this variable does not meet the requirements of reliability and validity. Based on calculations using factor analysis there are 21 variables that were grouped into seven factors, namely, the product factor, the price factor, the factor of physical evidence, the people factor, factor reference group, motivation, and personal factors. Of the seven factors are factors of physical evidence and the product is the dominant factor that can affect a student's decision to go to college at the University Pamulang. Keywords: Analysis, Determinants, Decision Students, Choosing, University Pamulang